Linking Up : Public-Private Partnerships in Power Transmission in Africa - World Bank Group (World Bank, Washington, DC, 2017)
The 'Linking up: Public-Private Partnerships in Power Transmission in Africa' report examines private sector-led investments in transmission globally and how this approach is applicable in sub-Saharan Africa. The private sector has invested over US$25 billion in the generation sector in Africa, and across other regions, has also participated successfully in transmission networks in many countries in Latin America and Asia. In these regions, private sector participation has reduced project costs and expanded coverage. The report draws lessons from case studies and highlights what regulations and other factors are needed to attract private sector interest in transmission projects.